Anti-thermal grain growth in SrTiO3: Coupled reduction of the grain boundary energy and grain growth rate constant. (1st May 2018) - Kelly, Madeleine N.; Rheinheimer, Wolfgang; Hoffmann, Michael J.; Rohrer, Gregory S.
Abstract: The dihedral angles at grain boundary thermal grooves in SrTiO3 were measured and used to determine the relative grain boundary energy at several temperatures where the grain growth rate constant displays anti-thermal properties (it decreases with increasing temperature). The measurements indicate that at temperatures in the anti-thermal region (1390 °C–1400 °C), the average grain boundary energy is less than at a lower temperature (1350 °C) where grain boundaries move more rapidly. Three-dimensional electron backscatter diffraction was used to measure the geometries of internal triple junctions in a sample where the slow and fast grain boundaries co-exist. Based on the dihedral angles at triple junctions, the ratio of the energies of slow boundaries to fast boundaries is 0.86. The results indicate that at temperatures between 1350 °C and 1425 °C, the higher and lower energy boundaries coexist. The coexistence of the two boundary types in this temperature range is likely because there is a range of grain boundary energies and the temperature at which a boundary transforms from the slow type to the fast type depends on its grain boundary energy. Graphical abstract: Image 1